Cadmium effects on the organization of actin filaments in Arabidopsis thaliana primary root cells - Goriunova, I. I.; Krasylenko, Yu.A.; Zaslavsky, V.A.; Yemets, A. I. (Reports of the National Academy of Sciences of Ukraine, 2014)
The effects of cadmium (Cd2+) as a widespread soil pollutant on the organization of plant actin filaments have not been elucidated. It is revealed that CdSO4 inhibits the growth of Arabidopsis thaliana (GFP-FABD2) primary roots that is accompanied by morphological alterations and disturbances of actin filaments organization in primary root cells. It is found that the treatment of seedlings with NdSO4 (5–20 µM) lead to the reorientation and/or depolymerization of actin filaments in cells of the meristematic, transition, and elongation root zones. Hence, actin filaments are supposed to be one of the intracellular targets for Cd2+ in the realization of cellular mechanisms of its phytotoxicity.